Eastern Sudan in its setting : the archaeology of a region far from the Nile Valley - Manzo, Andrea (Cambridge monographs in African archaeology, 2017)
Ongoing research in Eastern Sudan has provided a preliminary reconstruction of the history of the region from c. 6000 BC to AD 1500. This publication outlines this reconstruction and also considers the more general setting known for the other regions of northeastern Africa.